Marathi Cinema as a Political Text: Reflecting Maharashtra's Ideological Landscape - Patil, Nilesh Aatmaram; Gondhali, Chandrakant (Research Review Journal of Social Science, 2025)
Marathi cinema, as the oldest film industry in India with origins dating back to Dadasaheb Phalke's Raja Harishchandra (1913), has consistently functioned as more than mere entertainment. This research paper examines how Marathi cinema serves as a cultural mirror reflecting and shaping the complex political ideologies of Maharashtra. Through analysis of films from the silent era to contemporary productions, the paper identifies different dominant ideological streams such as right wing and left-wing ideologies, conservative and liberal views, experimental and contemporary opinions, hegemonic nationalism, anti-caste and social justice movements, regional identity politics centred on Marathi linguistic and cultural assertion; and contemporary power politics addressing corruption and leadership. The cinematic medium has proven particularly influential in constructing historical narratives about Maratha rulers like Chhatrapati Shivaji, whose legacy remains hotly contested by different political factions. By examining these cinematic representations across different historical periods, this paper demonstrates how Marathi films both respond to and actively shape Maharashtra's political consciousness, serving as a battleground where competing visions of society, history, and identity are negotiated and contested.